Argentina Tercer Mundo: Nueva izquierda, emociones y política revolucionaria en las décadas de 1960 y 1970 - Manzano, Adriana Valeria (2014)
This article analyzes the emergence and spread of an assimilation of Argentina with the Third World. It contends that “thirdworldism” was a key component of the ideas and practices of Argentina’s New Left. The political and cultural actors that coalesced into that New Left focused on the contrasts between “modernizing” spaces and phenomena, and the grievous living and working conditions in the provinces of the Northeast and the Northwest. These latter helped question the modernizing narratives at the same time that they contributed to approach Argentina to the usual images of the “geography of rebellion” of the Third World. The focus on the contrasts also allowed for the shaping of a collective emotion, indignation, which in turn heightened ideological beliefs and politico-cultural practices. The first segment explores the making of the parameters of “indignation” in its linkages with the emphasis on social, geographical, and economic contrasts. The second segment reconstructs the travel practices and cultural consumptions of a cohort of young people who experienced their political socialization in the intersection of the 1960s and 1970s. Many of the youths involved in those initiatives believed that Peronism represented the best way to a national and social “liberation” that they thought was impending. The last segment analyzes the juncture of 1973 as a “Thirdworliest spring”.